Total Synthesis of Keramaphidin B and Ingenamine - Kurihara, Yuki; Yagi, Minori; Yoshimura, Sho; Ito, Kenta; Shimotani, Yuta; Uematsu, Miyuna; Noguchi, Takashi; Yasufuku, Haruka; Okita, Ayane; Fukaya, Keisuke; Oishi, Takeshi; Kawahara, Ryota; Simizu, Siro; Chida, Noritaka; Okamura, Toshitaka; Sato, Takaaki (Synthesis, 2025)
The full details of the total synthesis of keramaphidin B and ingenamine are reported herein. The most conspicuous transformation in our total synthesis is the base-catalyzed Diels–Alder reaction using dynamic regioselective crystallization (alternatively referred to as crystallization-induced transformation). The tertiary alcohol, which is used for the base-catalyzed activation in the Diels–Alder reaction, is removed as its p-fluorobenzoate using SmI2 (HMPA)4. Double macrocyclic alkylation enables the regioselective construction of two macrocycles in a single step. The developed sequence is highly efficient, achieving the unified total synthesis of keramaphidin B and ingenamine within 13 steps from commercially available compounds. Our biological study elucidated the significant role of the two macrocycles in their antiproliferative effects against human cancer cell lines.
Keywords: Diels–Alder reaction; Dynamic crystallization; Macrocycle; Manzamine alkaloids; Total synthesis; Crystallization-induced transformation